Realities and challenges of port alliance in Japan — Ports of Kobe and Osaka - Inoue, Satoshi (Research in transportation business & management, 2018)
Japanese ports have played a unique twofold role, managing marine terminals and at the same time developing seafront of their port cities for multiple uses. Due to this duality in role, ports are considered inseparable from the city's overall management, leading to port management by general local administration. Increasing competition with ports of East Asian counties, however, has compelled the national government to press major ports to make their terminals more efficient and competitive. Under the latest national port policy, Kobe and Osaka joined forces to form up the first strategic port alliance in the country. They established a joint port company in 2014 to manage their terminals in an integrated way. This paper investigates the Kobe-Osaka port alliance to assess how it works in reality and also discusses challenges and business opportunities. It is based on intensive interviews together with an overview of the historical evolution of Japan's container port policy and also a comparative analysis with recent cases of port alliance around the world. For Kobe and Osaka, in order to make the most of the synergy of this alliance, strengthening the autonomy of the port company and implementing a range of logistics strategies are important issues.